Safety, tolerability, pharmacokinetics, and pharmacodynamics of a soluble guanylate cyclase stimulator, HEC95468, in healthy volunteers: a randomized, double-blinded, placebo-controlled phase 1 trial - Gui, Yu-zhou; Wang, Wei; Wu, Qing-qing; Ding, Qi-chen; Qian, Hong-jie; Lu, Qiu-bei; Zhang, Ying-jun; Zhuang, Yu-lei; Deng, Li; Zuo, Ying-lin; Luo, Lin; Jia, Jing-ying (Frontiers in Pharmacology, 2024)
Heart failure is the most costly cardiovascular disorder. New treatments are urgently needed. This study aims to evaluate the safety, pharmacokinetics, and pharmacodynamic profile of HEC95468, a soluble guanylate cyclase (sGC) stimulator, in healthy volunteers. Sixty-two, eighteen, and forty-eight participants were enrolled in the single ascending dose (SAD) study, the food effect (FE) study, and the multiple ascending dose (MAD) study, respectively. The study conforms to good clinical practice and the Declaration of Helsinki. Overall, HEC95468 was safe and tolerable; a higher proportion of HEC95468-treated participants reported mild headaches, dizziness, decreased blood pressure, increased heart rate, and gastrointestinal-related treatment-emergent adverse events (TEAEs), similar to the sGC stimulators riociguat and vericiguat. In terms of pharmacokinetic parameters, the maximum observed plasma concentration (Cmax) and the area under the concentration-time curve (AUC0-t) were dose-proportional over the dose range. Moderate accumulation was observed after multiple administrations of HEC95468. Systolic blood pressure (SBP) and diastolic blood pressure decreased, while 3′,5′-cyclic guanosine monophosphate (cGMP) concentration in plasma increased and heart rate was induced. Vasoactive hormones (renin, angiotensin II, and norepinephrine) in plasma were compensatorily elevated after oral administration. These data supported further clinical trials of HEC95468 in the treatment of heart failure and pulmonary arterial hypertension. Systematic Review Registration:http://www.chinadrugtrials.org.cn, identifier CTR20210064.